2022
DOI: 10.3389/fgene.2022.929293
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel biomarkers in septic cardiomyopathy via integrated bioinformatics analysis and experimental validation

Abstract: Purpose: Septic cardiomyopathy (SCM) is an important world public health problem with high morbidity and mortality. It is necessary to identify SCM biomarkers at the genetic level to identify new therapeutic targets and strategies.Method: DEGs in SCM were identified by comprehensive bioinformatics analysis of microarray datasets (GSE53007 and GSE79962) downloaded from the GEO database. Subsequently, bioinformatics analysis was used to conduct an in-depth exploration of DEGs, including GO and KEGG pathway enric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Studies have shown that it is necessary to combine clinical, electrocardiographic, hemodynamic parameters and echocardiography and other methods to fully diagnose SCM [27]. Previous studies have identified novel biomarkers in SCM by differential analysis and protein-protein interaction network analysis [28]. For the first time, our study combined difference analysis, WGCNA and machine learning algorithms to screen potential biomarkers of SCM.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that it is necessary to combine clinical, electrocardiographic, hemodynamic parameters and echocardiography and other methods to fully diagnose SCM [27]. Previous studies have identified novel biomarkers in SCM by differential analysis and protein-protein interaction network analysis [28]. For the first time, our study combined difference analysis, WGCNA and machine learning algorithms to screen potential biomarkers of SCM.…”
Section: Discussionmentioning
confidence: 99%